Entrepreneurial social network modelling on business performance of Malay entrepreneurs in Malaysia / Ehsan Fansuree Mohd.Surin, Nurul Hafez Abd. Halil and Oswald Timothy Edward - Mohd.Surin, Ehsan Fansuree; Abd. Halil, Nurul Hafez; Oswald, Timothy Edward (Research Management Institute (RMI), 2014)
The purpose of this study is to explore social network among Malay entrepreneurs of SME firms in manufacturing industry in Malaysia. Specifically, this research aims to investigate the usage of social network among Malay entrepreneurs. Secondly, this research aims to investigate the relationship between social network and business performance among Malay entrepreneurs. The research data were collected through mail and self-administered questionnaire sent to owner-manager around Malaysia. A stratified random sampling was used which elicited 198 useable responses for data analysis. A descriptive analysis was carried out to ascertain the usage of social network whilst eight hypotheses were formulated for hypotheses testing. Four hypotheses were examined the direct impact of social network on financial business performance variables meanwhile another four hypotheses were formulated to examine the direct impact of social network on non-financial business performance. All hypotheses were tested by using hierarchical multiple regressions. The results revealed that (1) network centrality has significant positive relationship with non-financial aspects of business performance; (2) network centrality has positive relationship but not achieve a valid significance level; (3) network size, network activity and network density do not affect significantly both financial and non-financial aspects of business performance. This study enriches the body of knowledge in the area of entrepreneurship by providing the information as the use and impact of social network in Malaysian SMEs. The findings can be used also by the entrepreneurs in shaping their strategic decision for better business achievement. It is hoped that, this study will attract the attention of academicians to make further research in the social network theme especially in a developing country like Malaysia.